Risk Factors and Outcomes of Acute Myocardial Infarction in a Cohort of Antiphospholipid Syndrome - Gan, Yuzhou; Zhao, Yawei; Li, Gongming; Ye, Hua; Zhou, Yunshan; Hou, Chang; Wang, Lan; Guo, Jianping; Li, Chun (Frontiers in Cardiovascular Medicine, 2022)
Background Antiphospholipid syndrome (APS) is a disorder associated with thromboembolic diseases, including acute myocardial infarction (AMI). Given that AMI is a relatively common condition with poor prognostic features, identification of risk factors for AMI in APS is important. Methods A retrospective cohort study was performed consisting of 332 patients with APS, and 239 patients with thrombotic APS were finally included. Patients were followed up in the outpatient department for 5 years. Clinical data and laboratory parameters were analyzed to identify the risk factors for AMI in APS. The primary and secondary clinical outcomes were all-cause mortality and recurrence of thrombosis, respectively. Results AMI was observed in 12.1% (29/239) of patients with APS. Compared to patients without AMI, patients with AMI had multiple organ thrombosis (55.1 vs. 34.3%, p = 0.029), recurrent thrombosis (58.6 vs. 34.3%, p = 0.011), a higher incidence of atherosclerosis (62.1 vs. 23.8%, p < 0.001), higher neutrophil count (×109/L) [4.68 (3.25, 8.17) vs. 3.71 (2.64, 5.80), p = 0.036], longer QT interval (ms) [438 ms (423, 454) vs. 425 ms (410, 446), p = 0.016], and fewer venous thrombosis events (27.6 vs. 63.3%, p < 0.001). Multivariate logistic regression analysis (adjusted for age and gender) identified several factors that were positively associated with AMI, including multiple organ thrombosis [odds ratio (OR) 8.862, 95% confidence interval (CI): 1.817–43.212, p = 0.007), atherosclerosis (OR 5.397, 95%CI: 1.943–14.994, p = 0.001), and elevated neutrophil count (>6.3 ×109/L) (OR 3.271, 95%CI: 1.268–8.440, p = 0.014). The venous thrombosis was negatively associated with AMI (OR 0.106, 95%CI: 0.036–0.314, p < 0.001). Kaplan–Meier analysis revealed that the recurrence rates of arterial thrombosis differed significantly between patients with AMI and those without AMI [hazard ratio (HR) = 3.307, p = 0.038]. Conclusion Atherosclerosis, multiple organ thrombosis, an increased number of neutrophils are variables positively associated with AMI in APS, and venous thrombosis had a negative association with AMI. AMI only predicts the subsequent recurrence of arterial thrombosis. These findings suggest that distinct pathophysiological mechanisms may exist and contribute to the development of venous or arterial thrombotic APS.